Boron containing metal–organic framework for highly selective photocatalytic production of H2O2 by promoting two-electron O2 reduction. Issue 10 (6th September 2021) - Li, Yujie; Ma, Fahao; Zheng, Liren; Liu, Yuanyuan; Wang, Zeyan; Wang, Peng; Zheng, Zhaoke; Cheng, Hefeng; Dai, Ying; Huang, Baibiao
Abstract : The adsorption sites of boron in UiO-66-B lead to in a larger amount of O2 adsorption; and the H + is adsorbed on the oxygen adjacent to boron, which is more conducive to the proton coupling reaction of ˙O2 − to H2 O2 in the second step. Abstract : A zirconium-based metal–organic framework containing boron (UiO-66-B) is prepared, which displays efficient photocatalytic H2 O2 production. The H2 O2 evolution rate is about 1002 μmol g −1 h −1, much higher than that of most known photocatalysts. Pristine UiO-66 displays a much lower activity (314 μmol g −1 h −1 ) under the same conditions, suggesting the significant role of boron. Both theoretical calculations and the combined experimental results verify the above conclusion, and the role of boron is ascribed to the following aspects: (1) enhanced O2 adsorption, (2) highly selective proton-coupled two-electron transfer, (3) faster carrier separation and surface charge transfer, and (4) faster generation but slower decomposition rates of H2 O2 . This work highlights key factors in the two-electron O2 reduction reaction (ORR), presents a deeper understanding of the role of boron in enhancing H2 O2 production, and provides a new strategy for designing photocatalysts with excellent H2 O2 evolution efficiency.